The effects of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) on the transcriptome of aryl hydrocarbon receptor (AhR) knock-down porcine granulosa cells - Ruszkowska, Monika (PeerJ, 2020)
BACKGROUND: 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) is a toxic man-made chemical, adversely affecting reproductive processes. The well-characterized canonical mechanism of TCDD action involves the activation of aryl hydrocarbon receptor (AhR) pathway, but AhR-independent mechanisms were also suggested. By applying RNA interference technology and Next Generation Sequencing (NGS) we aimed to identify genes involved in the mechanism of TCDD action in AhR knock-down porcine granulosa cells. METHODS: Porcine granulosa cells were transfected with small interfering RNAs targeting mRNA of AhR. After transfection, medium was exchanged and the AhR knock-down cells were treated with TCDD (100 nM) for 3, 12 or 24 h, total cellular RNA was isolated and designated for NGS. Following sequencing, differentially expressed genes (DEGs) were identified. To analyze functions and establish possible interactions of DEGs, the Gene Ontology (GO) database and the Search Tool for the Retrieval of Interacting Genes (STRING) database were used, respectively. RESULTS: The AhR gene expression level and protein abundance were significantly decreased after AhR-targeted siRNAs transfection of the cells. In TCDD-treated AhR knock-down cells we identified 360 differentially expressed genes (DEGs; P-adjusted < 0.05 and log2 fold change [log2FC] ≥ 1.0). The functional enrichment analysis of DEGs revealed that TCDD influenced the expression of genes involved, among other, in the metabolism of vitamin A, follicular development and oocyte maturation, proliferation and differentiation as well as inflammation, stress response, apoptosis and oncogenesis. The three-time point study demonstrated that TCDD-induced changes in the transcriptome of AhR knock-down porcine granulosa cells were especially pronounced during the early stages of the treatment (3 h). CONCLUSIONS: TCDD affected the transcriptome of AhR knock-down porcine granulosa cells. The molecules involved in the AhR-independent action of TCDD were indicated in the study. The obtained data contribute to better understanding of molecular processes induced by xenobiotics in the ovary.